746. Comparing Hospital Course in Hospitalized Patients Infected with Babesiosis Versus Patients Coinfected with Lyme Disease and Babesiosis. (31st December 2020) - Spector, Rachel; Lum, Michael D; Papamanoli, Aikaterini; Reardon, Kelsey; Garry, Evan; Marcos, Luis
Abstract: Background: Research is currently lacking on the interplay between Babesiosis and Lyme disease (LD) and how this coinfection may translate into morbidity and mortality. The aim of this study is to compare the clinical features of patients with single-infection with Babesia microti to those co-infected with Borrelia burgdorferi and Babesia microti. Methods: A retrospective review of all adult patients diagnosed with babesiosis and tested for LD at Stony Brook University Hospital between 2014 and 2019 was performed (n=40). Patients with single babesia infection (Group 1, n=22) were compared to those with Babesia and LD (Group 2, n=18). Babesiosis diagnosis was determined by microscopic visualization of Babesia spp under peripheral blood smear, and confirmed by PCR for B. microti . LD inclusion criteria included a positive screened ELISA test for lyme followed by positive IgM antibody by western blot per CDC criteria (2-3 positive bands). Statistical analysis of the data involved Fisher exact test, Chi-square test, independent t-test, and Wilcoxon rank sum tests. Statistical significance was considered as a p-value less than 0.05. Results: There was no significant difference in gender, race, and age (p >.75) between both groups as well as comorbidities including hypertension, diabetes, heart conditions, and immunocompromised state (p=1.0). Maximum parasitemia (Group 1: 1.1%, Group 2: 1.7%, p= 0.26) and percentage admitted to the ICU (Group 1: 18.18%, Group 2: 22.22%, p=1.0) were similar among both groups. While lab values on admission including WBC, hemoglobin, platelets, LDH, ALT, and AST did not significantly differ (p >.09), the length of hospital stay in group 2 was significantly longer than group 1 (Group 1: 3.0 days, Group 2: 5.5 days; p=0.03). There was a 0% mortality rate among both groups. Table 2: Biomarkers of Patients Monoinfected with Babesiosis Versus Patients Coinfected with Babesiosis and Lyme Disease. Table 1: Demographics of Patients Monoinfected with Babesiosis Versus Patients Coinfected with Babesiosis and Lyme Disease. Conclusion: It is remarkable that despite no differences in lab values on admission, comorbidities, and demographics, patients with a coinfection had a longer hospital stay than those with only babesiosis. This suggests that having a coinfection with babesiosis and LD may lead to a more severe illness than a single infection with babesiosis. Disclosures: All Authors : No reported disclosures